Implementation of Docker and Continuous Integration / Continuous Delivery for Management Information System Development - AKBAR DHANY (NAROTAMA UNIVERSITY, 2020)
A series of Development and Operations (DevOps) in the process of making the Narotama University Management Information System have not been implemented properly by previous developers. There are improvements or additional features of the Management Information System that are in accordance with the functionality and the increasing development needs that will be used by the academic community, so that the Management Information System developer has a little difficulty in integrating documents and distributing applications with different packages to the Production Server. In this study, a new system design is proposed by applying the practice of Continuous Integration / Continuous Delivery as a document integration process and can simplify the application distribution process, as well as implementing the Docker Container Platform as an application container with different packages that can be run on production server together. The results of implementing the practice of Continuous Integration / Continuous Delivery and the implementation of the Docker Container Platform are able to help integrate documents between developers and be able to release fixes and add features packaged in different containers automatically and periodically without long delays. which only takes an average of 17.9 seconds in the process of sending the application to the Production Server.